A 1, 8-naphthalimide-based chemosensor with an off-on fluorescence and lifetime imaging response for intracellular Cr3+ and further for S2−. (March 2016) - Yu, Mingming; Du, Weiwei; Zhou, Wan; Li, Haixia; Liu, Chunxia; Wei, Liuhe; Li, Zhanxian; Zhang, Hongyan
Abstract: A novel 1, 8-naphthalimide-based chemosensor was designed and synthesized for rapid recognition of Cr 3+ . The desired sensor showed off-on fluorescent and lifetime-based response upon Cr 3+ and S 2− in solution, on test paper and in cells. With the intensity-based method, the limit of quantification (LOQ) value was 0–5.5 × 10 −5  M and the detection limit could be as low as 0.60 ppm. The ' in situ ' prepared Cr 3+ complex can recognize S 2− among a series of common anions with high selectivity and sensitivity, the LOD can be as low as 307 nM. The lifetime of the sensor changes from 4.95 to 4.89 and further to 5.88 ns upon addition of Cr 3+ and S 2− in turn. Graphical abstract: The fluorescence and lifetime change of the chemosensor and the ' in situ ' prepared Cr 3+ complex upon addition of Cr 3+ and S 2− on test paper and in living cells have been successfully demonstrated. Highlights: A Cr 3+ selective fluorescent "off-on" and lifetime-based chemosensor was synthesized. The chemosensor was capable of quantitatively detect the concentration of Cr 3+ by a dramatically enhanced fluorescence. The ' in situ ' prepared Cr 3+ complex showed high selectivity and sensitivity toward S 2− . The calculated low detection limit (LOD) value is as low as 307 nM for S 2− . The lifetime changed from 4.95 to 4.89 ns upon the addition of Cr 3+, and further increased to 5.88 ns upon addition of S 2− .